(untitled) (Fiep Bulletin - online, 2013)
Workplace Gymnastics is a tool that seeks to improve the well-being, satisfaction and quality of life of employees through physical activities at their own work environment. It minimize the effects caused by work activities on the musculoskeletal system. This study aimed to examine the effects of a program of Workplace Gymnastics on the quality of life of employees of a private institution in Porto Alegre. Workplace Gymnastics sessions were performed for 15 minutes,3x per week, for 8 months. The experimental methodology was characterized before and after the study with only one group. Survey participants were in agreement with resolution 196/96 of the National Health Council For data collection. We used the closed questionnaire adapted from Poleto (2002). The sample consisted of 30 employees working 8 hours per day. The results showed that employees improved their lifestyle after the Workplace Gymnastics Program. In relation to their general physical condition, there was an increase of 13% of employees feeling no physical discomfort and generally in all other related items there was a significant improvement. The employees demonstrated a greater willingness to work. From the results, it is concluded that the Workplace Gymnastics program influenced employees by changing their lifestyle. It was also noticed that there was a considerable decrease in the frequency of muscle discomfort and a greater willingness to work. In conclusion, it is suggested to continue the Workplace Gymnastics program, as well as the ergonomic analysis of workstations.